1997
DOI: 10.1017/s0022215100137685
|View full text |Cite
|
Sign up to set email alerts
|

Surgical management of bilateral immobile vocal folds and long-term follow-up

Abstract: Sixty-one cases of bilateral immobile vocal folds were classified as traumatic (52.46 per cent), idiopathic (39.34 per cent) or iatrogenic (8.20 per cent). During follow-up the idiopathic group of patients had a better prognosis (p<O.O5) compared to the traumatic or iatrogenic group. A spontaneous recovery was seen in 58.33 per cent of cases in the idiopathic group, 56.25 per cent in the traumatic group and 40.0 per cent in the iatrogenic group within a period of one year. Patients who failed to show sponta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 13 publications
1
10
0
Order By: Relevance
“…6 Some authors found a relationship between the injured nerve and the position of the paralyzed vocal fold 1,7 ; whereas, in other studies, 8,9 this relationship was not observed. Researchers have also reported that the position of the paralyzed vocal fold can be affected by the degree of reinnervation and that there is a possibility of regeneration in the recurrent laryngeal nerve.…”
Section: Introductionmentioning
confidence: 89%
“…6 Some authors found a relationship between the injured nerve and the position of the paralyzed vocal fold 1,7 ; whereas, in other studies, 8,9 this relationship was not observed. Researchers have also reported that the position of the paralyzed vocal fold can be affected by the degree of reinnervation and that there is a possibility of regeneration in the recurrent laryngeal nerve.…”
Section: Introductionmentioning
confidence: 89%
“…In literature different techniques were compared in management of patient with bilateral paralysis of the vocal cords for example microsurgical arytenoidectomy through a mid-line thyrotomy, endolaryngeal microsurgical arytenoidectomy, endoscopic laterofixation of vocal cords, laser CO 2 cordotomy or endoscopic posterior costal cartilage graft [7][8][9]11]. In our opinion endoscopic vocal cord laterofixation is effective primary procedure for pediatric vocal cord paralysis.…”
Section: Discussionmentioning
confidence: 99%
“…Thirty-two articles were not original research papers (narrative reviews, case reports or editorial letters) [10,. Eighteen articles reported adult or mixed adult and pediatric population without a separate analysis [49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66]. Sixteen articles had flaws that disqualified them from inclusion (sampling, diagnostic definition, incomplete follow up, and non-objective assessment of final outcome) [2,4,[6][7][8]14,[67][68][69][70][71][72][73][74][75][76].…”
Section: Electronic Search and Study Selectionmentioning
confidence: 99%
“…Holl-Allen [37] Letter to editor 43 Sardana [38] Case reports 44 Kiger et al [36] Case report 45 Lerner et al [39] Case report with discussion 46 King and Blumin [40] Narrative review 47 Mancuso [41] Narrative review 48 Maturo and Hartnick [42] Narrative review, discussing LEMG technique 49 Roger et al [43] Narrative review 50 Rubin and Sataloff [44] Narrative review 51 Sichel et al [45] Narrative review [117]. Additionally, inhalational agents may affect muscle function, casting doubt on the diagnosis on many occasions [118].…”
Section: No Studymentioning
confidence: 99%
See 1 more Smart Citation